PENGARUH MOTIVASI TERHADAP KINERJA KARYAWAN DENGAN PENGEMBANGAN KARIR SEBAGAI VARIABEL INTERVENING PADA UNIVERSITAS “XYZ” DI SURABAYA - Rahayu, Tri Annisa Setya; Fatimah, Nuzulul; Putra, Riyan Sisiawan (STIE Mahardhika, 2025)
This study aims to analyze the effect of work motivation on employee performance, with career development as an intervening variable at XYZ University in Surabaya. This research adopts a quantitative approach using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method and involves 143 education personnel as the sample. Data were collected through a structured questionnaire and analyzed using SmartPLS software. The results show that work motivation has a positive and significant effect on career development, indicating that highly motivated education personnel are more responsive to career development opportunities. Career development is also proven to have a significant impact on employee performance, suggesting that a well-structured career development program can enhance work quality. Work motivation has a direct influence on performance, demonstrating that high motivation drives employee productivity and responsibility. Furthermore, career development significantly mediates the relationship between work motivation and performance, implying that work motivation has a greater impact on performance in the presence of effective career development. This study concludes that the synergy between work motivation and career development is crucial for improving the performance of education personnel at XYZ University. It is recommended that the organization provide transparent and equitable career development programs and foster a work environment that supports motivation. This study offers practical contributions to human resource management in the higher education sector.